2011
DOI: 10.1002/ejoc.201001318
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity in Electrophilic Aromatic Substitution: Insights from Interaction Energy Decomposition Potentials

Abstract: The S E Ar reaction was scrutinized using a quantitative, fragment-based interaction energy decomposition analysis (EDA) as implemented in the ADF program. The interaction energy between monosubstituted benzene derivatives and a model electrophile at the onset of the reaction was studied and decomposed into Pauli repulsion, electrostatic interaction and orbital interaction terms for a plane parallel to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
1
15
0
2
Order By: Relevance
“…To determine the intrinsic reactivity of linear acenes and the dependency of the reaction on the length of the acene, the interaction of the acene with an incoming electrophile was probed as outlined above. We established in our earlier study, concerning the orientation rules of S E Ar reactions,24 that the spherical and closed shell copper(I) is an ideal model soft electrophilic reagent that is capable of reliably characterizing the electrophilic reactivity of substituted aromatic systems. Moreover, we tested the consistency and regioselectivity‐predicting ability of our protocol in the latter study and established an ideal substrate–reagent distance, which can be used with confidence in the scanning procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the intrinsic reactivity of linear acenes and the dependency of the reaction on the length of the acene, the interaction of the acene with an incoming electrophile was probed as outlined above. We established in our earlier study, concerning the orientation rules of S E Ar reactions,24 that the spherical and closed shell copper(I) is an ideal model soft electrophilic reagent that is capable of reliably characterizing the electrophilic reactivity of substituted aromatic systems. Moreover, we tested the consistency and regioselectivity‐predicting ability of our protocol in the latter study and established an ideal substrate–reagent distance, which can be used with confidence in the scanning procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Our methodology for evaluating the intrinsic reactivity of linear acenes is straightforward and was presented previously24 for the case of substituted benzene derivatives: for electrophilic reactivity, as illustrated in Figure 1, a model soft electrophile,24,25 is moved along a rectangular grid parallel to the plane of the acene, and the interaction energy between the aromatic system and the electrophile is determined in every point of the grid. The origin of the grid, [0,0], was set to the center of mass of the acene, and axes x and y were chosen to be perpendicular and parallel with the C1–C2 bond, respectively (see Scheme for numbering in anthracene).…”
Section: Methodology and Computational Detailsmentioning
confidence: 99%
“…Although π complex formation shifts the electron densities at the different ring positions, V C of the initial reactants may, nevertheless, be related to reactivity. In this regard, a recent83 theoretical interaction energy decomposition analysis of the S E Ar reaction found that intrinsic properties of both the aromatic reactant and the electrophile can be used as reactivity and regioselectivity indicators.…”
Section: The Electrophile Affinity Indexmentioning
confidence: 99%
“…As every fresh organic chemistry student learns, both inductive as well as resonance or mesomeric components are usually invoked to rationalize the experimentally observed behavior. Rules to predict the ortho -/ para - or meta -orienting ability of substituents are an active topic in chemical research and have been recovered from almost every imaginable point of view [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]; and even the EAS reaction mechanism is still under debate [ 30 , 42 , 43 , 44 , 45 , 46 , 47 ]. Among the various previous approaches for EAS study, we are especially interested in the ELF due to its direct relation with the BCM model and the IQA-ELF coupling.…”
Section: Introductionmentioning
confidence: 99%